Visibility Paradox in Digital Representation of Tradisional Foi Doa Music: Paradoks Visibilitas dalam Representasi Digital Musik Tradisional Foi Doa - Dedy Setyawan; Hermania Bupu; Sena Radya Iswara Samino; Ferdinandus Bate Dopo; Kanzul Fikri (Universitas Negeri Surabaya, 2026)
Digital visibility in the Foi Doa instrument shows a shift in the way culture is understood in the digital space. Visual representation in digital media plays a strong role in directing the audience's perception of traditional practices. The Qualitative Digital Discourse Analysis (QDDA) method was used to analyze content and responses on two YouTube channels with different production styles. Observations are focused on comparisons between cinematic representations and everyday documentation. High audience engagement on cinematic videos does not develop into a deep musical understanding. The audience's response focuses more on the visual aspect than on the sound structure and spiritual function of the instrument. Simple documentation does not show a comparable level of interaction. These findings show the dominance of visual elements in shaping audience perception in the digital space. This condition is understood as the paradox of visibility, which is a situation when the expansion of reach through digitalization goes hand in hand with the simplification of meaning. In contrast to the concepts of mediatization and spectacularization that emphasize the changing form and dominance of media, the visibility paradox highlights specifically the tension between increased visibility and narrowing of the depth of meaning in digital consumption practices. Thus, digital representation not only expands access, but also limits the way culture is interpreted.